A qualitative study on preparedness requirements for responding to chemical, biological, radiological, and nuclear incidents in Iran - Hamid Karimi Kivi; Vahid Hadi; Saeed Nazari; Peyman Namdar; Mahboobeh Afzali (BMC Research Notes)
Abstract Background and purpose The sudden increase in the number of exposed individuals, diverse injuries, damage to health equipment, and disruptions in health services highlight the need for a structured response to radiological and nuclear incidents. This study aims to identify the requirements for responding to CBRN incidents in Iran. This research contributes to a deeper understanding of the complexities involved in CBRN preparedness and response in Iran, highlighting areas for potential improvement and policy development. Methodology This qualitative research conducted in 2023 involved semi-structured interviews with 32 specialists selected through purposive sampling until data saturation was reached. Thematic analysis was employed to analyze the data. Findings The requirements for responding to CBRN incidents were categorized into three main classes with nine subcategories: Training Effective training content, establishment of specialized training centers, identification of target audiences, educational needs assessment, and continuous education. Drills Implementation of various operational drills and their content. Emergency response planning Elements of response plans and evaluation of these plans. Conclusion Timely and appropriate responses from the health system during critical phases after such incidents are crucial for mitigating adverse health effects. This study provides insights into the necessary requirements for enhancing readiness in the health sector as Iran progresses towards adopting modern technologies.